Guidelines of the International Headache Society for Controlled Clinical Trials in Cluster Headache. (December 2022) - Schoenen, Jean; Snoer, Agneta Henriette; Brandt, Roemer B; Fronczek, Rolf; Wei, Diana Y; Chung, Chin-Sang; Diener, Hans-Christoph; Dodick, David W; Fontaine, Denys; Goadsby, Peter J; Matharu, Manjit Singh; May, Arne; et al.
In 1995, a committee of the International Headache Society developed and published the first edition of the Guidelines for Controlled Trials of Drugs in Cluster Headache. These have not been revised. With the emergence of new medications, neuromodulation devices and trial designs, an updated version of the International Headache Society Guidelines for Controlled Clinical Trials in Cluster Headache is warranted. Given the scarcity of evidence-based data for cluster headache therapies, the update is largely consensus-based, but takes into account lessons learned from recent trials and demands by patients. It is intended to apply to both drug and neuromodulation treatments, with specific proposals for the latter when needed. The primary objective is to propose a template for designing high quality, state-of-the-art, controlled clinical trials of acute and preventive treatments in episodic and chronic cluster headache. The recommendations should not be regarded as dogma and alternative solutions to particular methodological problems should be explored in the future and scientifically validated.